2014
DOI: 10.21236/ada613907
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Demographics of Marine Mammals in SOCAL Through Photo-Identification, Genetics, and Satellite Telemetry

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. SPONSOR/MONITOR'S REPORTMonterey, CA 93943-5122 NUMBER(S)NPS-OC-14-005CR DISTRIBUTION / AVAILABILITY STATEMENTApproved for public release; distribution is unlimited. SUPPLEMENTARY NOTESThe views expressed in this report are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 32 publications
5
17
0
Order By: Relevance
“…This animal moved in waters with an average depth of 548 m and performed dives of up to 400-500 m (Wells et al 2009). Three Risso's dolphins tracked in southern California moved in waters with an average depth of 900-974 m (Falcone & Schorr 2011). This does not mean the animals do not occur elsewhere, and certainly there are records of the species in deep oceanic waters and in shallow waters a great distance from the shelf edge.…”
Section: Are Risso's Dolphins Restricted To Continental Margins?mentioning
confidence: 99%
“…This animal moved in waters with an average depth of 548 m and performed dives of up to 400-500 m (Wells et al 2009). Three Risso's dolphins tracked in southern California moved in waters with an average depth of 900-974 m (Falcone & Schorr 2011). This does not mean the animals do not occur elsewhere, and certainly there are records of the species in deep oceanic waters and in shallow waters a great distance from the shelf edge.…”
Section: Are Risso's Dolphins Restricted To Continental Margins?mentioning
confidence: 99%
“…Specifically, movements have been observed between the Southern Ocean and the coasts of Chile, Brazil and South Africa (30–70°S; Brown ), between the Azores and Iceland (40–65°N; Silva et al. ), between the northwest coast of Mexico (central Baja California) and the west coast of the USA (northern California, 26–40°N; Falcone & Schorr ), between the Faroes and westward of the Bay of Biscay (46–62°N; Mikkelsen et al. ), and along the coasts of the western and eastern North Pacific (30–60°N; Mizroch et al.…”
Section: Discussionmentioning
confidence: 99%
“…). Recent satellite tagging conducted off the south‐western coast of the USA found that fin whales aggregated along the coast during autumn and winter, dispersed farther offshore during spring and summer, and used several areas year‐round (Falcone & Schorr ). None of the tagged fin whales travelled south of approximately 26°N (Falcone & Schorr ).…”
Section: Discussionmentioning
confidence: 99%
“…Whales were assigned to age and sex classes using a combination of behavioral (e.g., mother-calf associations), genetic (for individuals that were biopsy sampled during the study), and appearance data (e.g., erupted teeth, scarring rates) following methods described in Rosso, Balardini, Moulins, and Würtz (2011) and Coomber, Moulins, Tepsich, and Rosso (2016). Individual sighting histories were created through the comparison of captured individuals in each sighting to the accrued catalog, as described in Falcone and Schorr (2014).…”
Section: Field Work and Photo Identificationmentioning
confidence: 99%